Galaxy Zoo: star formation versus spiral arm number - Hart, Ross E.; Bamford, Steven P.; Casteels, Kevin R.V.; Kruk, Sandor J.; Lintott, Chris J.; Masters, Karen L. (Oxford University Press, 2017)
Spiral arms are common features in low-redshift disc galaxies, and are prominent sites of star formation and dust obscuration. However, spiral structure can take many forms: from galaxies displaying two strong ‘grand design’ arms to those with many ‘flocculent’ arms. We investigate how these different arm types are related to a galaxy's star formation and gas properties by making use of visual spiral arm number measurements from Galaxy Zoo 2. We combine ultraviolet and mid-infrared (MIR) photometry from GALEX and WISE to measure the rates and relative fractions of obscured and unobscured star formation in a sample of low-redshift SDSS spirals. Total star formation rate has little dependence on spiral arm multiplicity, but two-armed spirals convert their gas to stars more efficiently. We find significant differences in the fraction of obscured star formation: an additional ∼10 per cent of star formation in two-armed galaxies is identified via MIR dust emission, compared to that in many-armed galaxies. The latter are also significantly offset below the IRX–β relation for low-redshift star-forming galaxies. We present several explanations for these differences versus arm number: variations in the spatial distribution, sizes or clearing time-scales of star-forming regions (i.e. molecular clouds), or contrasting recent star formation histories.